2010
DOI: 10.1007/s00382-010-0816-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Arctic clouds during intervals of rapid sea ice loss

Abstract: We investigate the behavior of clouds during rapid sea ice loss events (RILEs) in the Arctic, as simulated by multiple ensemble projections of the 21st century in the Community Climate System Model (CCSM3). Trends in cloud properties and sea ice coverage during RILEs are compared with their secular trends between 2000 and 2049 during summer, autumn, and winter. The results suggest that clouds promote abrupt Arctic climate change during RILEs through increased (decreased) cloudiness in autumn (summer) relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 54 publications
9
67
0
Order By: Relevance
“…The increased LE and SH fluxes could play a role in the increased cloud cover in October through enhanced unstable atmospheric conditions and increased water vapor. These results are also consistent with previous studies (Blüthgen et al, 2012;Schweiger et al, 2008;Vavrus et al, 2011).…”
Section: Cloud Cover Changes Resulting From Reduced Sea Icesupporting
confidence: 94%
See 1 more Smart Citation
“…The increased LE and SH fluxes could play a role in the increased cloud cover in October through enhanced unstable atmospheric conditions and increased water vapor. These results are also consistent with previous studies (Blüthgen et al, 2012;Schweiger et al, 2008;Vavrus et al, 2011).…”
Section: Cloud Cover Changes Resulting From Reduced Sea Icesupporting
confidence: 94%
“…2d), although the change was not substantial. The largest increase in simulated cloud cover in October agrees with previous studies using satellite data and climate model simulations (Liu et al, 2012;Vavrus et al, 2011;Wu and Lee, 2012).…”
Section: Simulated Change Of Arctic Sea Ice and Cloudssupporting
confidence: 89%
“…On the basis of TOVS satellite data Schweiger et al (2008a) observed that the sea ice retreat is linked to a decrease in lowlevel cloud amount and a simultaneous increase in mid-level clouds. The results on increasing cloud cover are consistent with the ensembles of 21st century projections by Vavrus et al (2010), who found that clouds increased in autumn during periods of rapid sea ice loss.…”
Section: Clouds Precipitation and Evaporationsupporting
confidence: 89%
“…Some of these changes have been either directly or indirectly linked to clouds (Francis and Hunter, 2006;Kay et al, 2008;Liu et al, 2008;Perovich et al, 2008;Kay and Gettelman, 2009;Vavrus et al, 2011), although the mechanisms…”
Section: Introductionmentioning
confidence: 99%